Babylon of Egypt : the archaeology of old Cairo and the origins of the city - Sheehan, Peter (American Research Center in Egypt Conservation series, 2010)
Presents a history of old Cairo, known to the Romans as Babylon, based on new archaeological evidence gathered between 2000 and 2006, revealing continuous occupation between the 6th century BC and the present.